Organizational Justice: A Vision by Higher Education Academic Staff (Global Journal of Management and Business Research, 2015)
Organizational justice is a common concept and of great interest among high education professionals, because it represents equal opportunities and outcomes for all people. The objective of this paper is to determine the significant effect among the qualifying academic variables and the variables in organizational justice. The sample population was made up of 334 teachers and we used Moorman#x2019;s (1991) Organizational Justice Instrument. The main results show that the teachers within a range of 40 to 49 years old perceive a better distribution in the work-load. This could be explained because they have greater seniority in the institution.
Keywords: organizational; distributive; procedural and interactional justice